2014
DOI: 10.4314/ahs.v13i4.7
|View full text |Cite
|
Sign up to set email alerts
|

A review of the management of perforated duodenal ulcers at a tertiary hospital in south western Nigeria

Abstract: Background: Gastro-duodenal perforations are common and may complicate peptic ulcer disease. Management is often by surgical closure. Objective: To determine the patterns of presentation and mode of management of duodenal ulcer perforations. Methods: Retrospective review of patients with duodenal ulcer perforations seen at the Obafemi Awolowo University Teaching Hospital between June 2001 and July 2011. Patients' records were reviewed for demography, duration of disease, probable risk factors, type of surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
6
11
1
Order By: Relevance
“…For example, African cohorts from Nigeria, Kenya, Ethiopia, Tanzania and Ghana report of male rates from 6 to 13 times that of females, median age in the 40s, and a predominant duodenal location in up to 90%. 17 21 Similar patterns are reported from the middle East and Arab countries and parts of southern Asia. 22 – 25 …”
Section: Epidemiology Of Peptic Ulcer Disease and Its Complicationssupporting
confidence: 75%
“…For example, African cohorts from Nigeria, Kenya, Ethiopia, Tanzania and Ghana report of male rates from 6 to 13 times that of females, median age in the 40s, and a predominant duodenal location in up to 90%. 17 21 Similar patterns are reported from the middle East and Arab countries and parts of southern Asia. 22 – 25 …”
Section: Epidemiology Of Peptic Ulcer Disease and Its Complicationssupporting
confidence: 75%
“…This was similar to the observation in Ile-Ife and other Centres. [17][18][19] Everett et al in their study of 136 patients observed sex ratio of 6.5:1 with only 18 female patients, this study agrees with the result of present study of men predominance in perforated peptic ulcer cases and this was in agreement with the findings of other studies where the male to female ratio ranged from 3.3:1 to 9:1. [20][21][22] Svanes was of the view that in men, ulcer perforation incidence increased until about 1950 and declined thereafter.…”
Section: Discussionsupporting
confidence: 83%
“…Leak rates of 2-8% have been reported after perforation repair. 19,21,22 In the present study the fistula rate was 5%. These unfortunate patients have a 35% chance of mortality.…”
Section: Discussionsupporting
confidence: 48%
“…Etonyeaku et al from Nigeria reported 10:1, Chalya et al from Tanzania found a 13:1 ratio while Bali et al from India showed a ratio of 5:1. 19,20,28 The acid reducing procedures (vagotomy/ highly selective vagotomy) are used infrequently and in special circumstances only (e.g. in giant ulcers).…”
Section: Discussionmentioning
confidence: 99%